2022
DOI: 10.1001/jamanetworkopen.2021.42780
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With Relapse and Treatment of Myelin Oligodendrocyte Glycoprotein Antibody–Associated Disease in the United Kingdom

Abstract: IMPORTANCE Longer-term outcomes and risk factors associated with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) are not well established. OBJECTIVE To investigate longer-term risk of relapse and factors associated with this risk among patients with MOGAD. DESIGN, SETTING, AND PARTICIPANTS This large, single-nation, prospective cohort study was conducted among 276 patients with MOGAD at 5 health care centers in the UK. Data from January 1973 to March 2020 were collected from 146 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 26 publications
6
46
2
1
Order By: Relevance
“…According to these results, the age of the present patient could have been a risk factor for further relapses. Of note, in that study, relapsing ADEM was found only in patients aged <12 years 9 . They also reported that the clinical phenotype might influence relapses; optic neuritis has a significant higher risk of disease activity compared with those with transverse myelitis (HR 2.66).…”
Section: Discussionmentioning
confidence: 80%
“…According to these results, the age of the present patient could have been a risk factor for further relapses. Of note, in that study, relapsing ADEM was found only in patients aged <12 years 9 . They also reported that the clinical phenotype might influence relapses; optic neuritis has a significant higher risk of disease activity compared with those with transverse myelitis (HR 2.66).…”
Section: Discussionmentioning
confidence: 80%
“…Expectedly, patients can have other attacks compatible with MOGAD prior to, concurrent with, or after unilateral cortical FLAMES/UCCE (12). Maintenance immunotherapy should be considered in patients with MOGAD who have relapsing disease, although the optimal long-term treatment approach remains unclear (52)(53)(54)(55).…”
Section: Treatment Of Unilateral Cortical Flames/uccementioning
confidence: 99%
“…In up to 20% of MOGAD patients, associations were found between a possible trigger and a first MOGAD event [3,8,[42][43][44][45]. Temporal associations have been reported with N-methyl-d-aspartate receptor encephalitis, infections, including herpes simplex virus, Borrelia, Epstein-Barr as well as, more recently, severe acute respiratory syndrome coronavirus type 2 (SARS-sCoV-2) [8,[42][43][44][45][46][47] and, albeit less frequently, with vaccinations (mostly with SARS-CoV-2 vaccination but also with diphtheria, tetanus, pertussis, polio, and influenza vaccination) [3,8,[42][43][44][45]. Recent research has shown that post-vaccination ON in the presence of MOG-IgG is particularly severe, with around 50% of affected patients experiencing severe and debilitating vision loss [45].…”
Section: Mogad-on and Infectionsmentioning
confidence: 99%
“…Long-term treatment is recommended for patients at risk for relapse and current therapies comprise the off-label use of prednisolone, steroid-sparing immunosuppression with azathioprine, methotrexate, mycophenolate mofetil, rituximab and IVIG [75][76][77][78][79]. Maintenance treatment is given either as monotherapy or as combination therapy [9,38,42]. Current data do not show any indication for a relapseindependent disease progression, but the course of symptoms including visual quality of life over time from the patients' perspective need further investigation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%